Determination of colour removal in synthetic dye waste containing Megaperse Yellow YNA using inorganic coagulants / Wilsra Sugara - Sugara, Wilsra (Faculty of Applied Sciences, 2009)
In this study, chemical coagulation process was chosen as a mean of removing colour from synthetic dye waste of Megaperse Yellow YNA. Coagulants used were MgCl₂ and FeCl₃ and combination of both in which the effectiveness was studied in three parameters: pH, coagulant dosage and contact time. Dye waste treatment with MgCl₂ alone yielded unsatisfactory results with the maximum colour removal of only 39.94%. When treated with FeCl₃ under the most optimum conditions, a high efficiency of colour reduction of 90.24% was obtained. In the combination of both coagulants, a slightly increased percentage was achieved (91.20%) at optimum conditions of pH 8, 8 g/L of 1:1 ratio (w/w) and 180 minutes time settling.